The Biomedical Publications Industry Must Change to Better Serve the Needs of Science and Scientists - Michael Lederman; Neil Greenspan (Pathogens and Immunity)
The biomedical publications industry is vital to progress in science and health care. We observe that this industry has become unnecessarily complex and expensive for researchers and readers, impeding the sharing of research findings. In this perspective, we offer selected critiques of this industry and suggest how it might be improved.